From Intention to Action: How Boycott Motivation Influences Consumer Behavior toward Israel-Affiliated Brands - Andriani Kusumawati; Rasya Safira Ishamiyya (Journal of Consumer Sciences, 2025)
Background: The dynamics of global politics can profoundly impact international trade. The Israel–Palestine conflict has sparked renewed interest, prompting global criticism of Israel's human rights violations. The conflict has also sparked a boycott campaign in Indonesia. Purpose: This study examines the effects of motivations for boycotting, classified by trigger, promoters, and inhibitors, on boycott intentions and their impact on boycott behavior. Method: The study employs a quantitative research design and uses a purposive sample of 185 participants. Data were collected through a survey that distributed questionnaires to respondents. The data analysis employed descriptive statistics and Partial Least Squares-Structural Equation Modelling (PLS-SEM). Findings: The findings indicate a positive influence of subjective norms, self-enhancement, and perceived behavioral control on boycott intention. Counter-arguments demonstrate an adverse effect. Neither animosity nor brand image affects boycott intention. Firm boycott intention significantly impacts behavior. Conclusions: The study reveals that the primary factor affecting an individual’s intention to boycott is the ability to carry it out. Moreover, individuals who feel that boycotting can elevate their self-esteem are more inclined to participate. Research Implication: Companies should communicate more proactively. They should explain their stance on politics and issues without contradicting their values. Having clear ethics and empathy can help maintain consumer trust during boycotts.